2012
DOI: 10.1245/s10434-012-2353-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Gender Disparities and the Role of Primary Tumor Type on Inpatient Outcomes Following Craniotomy for Brain Metastases

Abstract: Evidence of race and gender disparities in outcomes were found in black patients, especially in black females who underwent surgical resection for brain metastases. These findings highlight an opportunity to reduce the gap of outcome disparities in brain metastasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
5
24
1
Order By: Relevance
“…On univariate analysis, patients who were uninsured or with Medicare/Medicaid vs. commercial insurance approached significance (13.7 vs. 6.8 months, p  = 0.080); however on multivariate analysis, insurance status was no longer a significant predictor of overall survival ( p  < 0.49). This lack of significance could be due in part to the number of patients included in our analysis compared to the numbers of patients in publications using registry data that showed a worse mortality in underinsured patients (10, 11), but it may also suggest that the primary drivers of potential health disparity in our patient population may be related to their presentation in a more advanced disease state (potentially with more active extracranial disease, lower PS, etc. ), rather than an inability to receive adequate care following GKRS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On univariate analysis, patients who were uninsured or with Medicare/Medicaid vs. commercial insurance approached significance (13.7 vs. 6.8 months, p  = 0.080); however on multivariate analysis, insurance status was no longer a significant predictor of overall survival ( p  < 0.49). This lack of significance could be due in part to the number of patients included in our analysis compared to the numbers of patients in publications using registry data that showed a worse mortality in underinsured patients (10, 11), but it may also suggest that the primary drivers of potential health disparity in our patient population may be related to their presentation in a more advanced disease state (potentially with more active extracranial disease, lower PS, etc. ), rather than an inability to receive adequate care following GKRS.…”
Section: Discussionmentioning
confidence: 87%
“…Many factors including tumor histology, control of extracranial disease, and PS impact a patient’s overall survival (8). It has been reported that uninsured and underinsured cancer patients often have delayed diagnosis and inferior outcomes (911). Our institutional series is unique in that a larger percentage of our patient population is African-American, on Medicaid or on Medicare compared to previous publications reporting health disparities in patients treated for brain metastases (10, 11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities based on race or ethnicity in neurooncology patients are well documented. 40,41,43 Prior evaluation of the Nationwide Inpatient Sample from 1988 to 2004 by Curry et al has suggested that postoperative disparities may be primarily due to more severe disease on presentation and reduced access to high-volume care. 17 However, these differences in length of hospital stay may also be related to residual confounding, as disparities in outcomes have also been shown to be attributable to a greater number of and more severe comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…10,22 Nuño et al found that African American patients had a higher inpatient mortality rate than white patients following craniotomy procedures. 15 In 2013, Stone et al demonstrated that African American children had an increased risk of in-hospital death following surgeries. 22 Racial disparities remain when discharge disposition is considered.…”
Section: Discussionmentioning
confidence: 99%